TINJAUAN YURIDIS TERHADAP PERANAN LEMBAGA PERLINDUNGAN SAKSI DAN KORBAN (LPSK) DALAM MELINDUNGI SAKSI DALAM TINDAK PIDANA KORUPSI - James Antro; Liza Erwina; Abul Khair (Jurnal Mahupiki, 2013)
ABSTRAKSI James Antro Yosua Panjaitan* Liza Erwina** Abul Khair*** The criminal Justice system in Indonesia stressed the importance of witness as primary factor to reveal criminal offence. But the appreciation of witness role was still too little. This can be seen in KUHAP was still not protecting the existence of a comprehensive witness. However with the born of Law No. 13 of 2006 about Protecting of Witness and Victims may be an alternative legal system in Indonesia which specifically regulate about protecting of witness. * Mahasiswa Departemen Hukum Pidana Fakultas Hukum Universitas Sumatera Utara. ** Dosen Pembimbing I. *** Dosen Pembimbing II.